Penerapan Model Pembelajaran Kooperatif Jigsaw Untuk Meningkatkan Minat Belajar Siswa - Subandi Pacitan (MGMP PAI SMP BINTAN, 2022)
This article focuses on the discussion of increasing student learning interest in the subject of Islamic Religious Education subject matter of the content of Surat Al Kaafiruun at the elementary school level in Bintan Regency. This study aims to determine the extent to which the Jigsaw cooperative learning model can increase students' interest in learning which in turn will improve their learning outcomes. To answer this question, this study used classroom action research with participants from class VI students. This research lasted for three months where researchers used three cycles in class action. The results of the data analysis showed that students experienced positive changes from before the action was taken. There was a significant increase in learning interest and learning outcomes after the action was taken. This study contributes to the PAI learning process in the future.